Integrasi Nilai-Nilai Pendidikan Agama Islam dalam Kegiatan Pesantren Ramadhan di SMPN 6 Kediri - Chairuddin, M. (Madrasah Ibtidaiyah Education Journal, 2025)
The purpose of this study was to examine the integration of Islamic Religious Education values ​​in the activities of the Ramadhan Boarding School at SMPN 6 Kediri and its impact on the formation of students' character. This study used a qualitative approach with a case study design to explore the integration of Islamic Religious Education values ​​in the activities of the Ramadhan Boarding School at SMPN 6 Kediri, with the subjects being the principal, Islamic Religious Education teachers, and students. Data were collected through in-depth interviews, observations, and documentation, which were then analyzed using qualitative techniques such as coding, categorization, and interpretation. To ensure the validity of the data, this study used triangulation techniques by comparing the results of interviews, observations, and documentation to maintain the consistency of the findings. The Ramadhan Boarding School at SMPN 6 Kediri has proven effective in integrating Islamic Religious Education values ​​into students' daily lives through activities such as tadarus Al-Qur'an, congregational dhuha prayers, and tausiyah. The positive impact can be seen from changes in student behavior who have begun to internalize religious values, such as honesty, discipline, and responsibility. This activity is also fully supported by the school, teachers, committee, and parents, which creates harmony between the curriculum and the goals of developing student character